Factors Associated with the Incidence of Contact Dermatitis among Fish Traders at the Aur Duri Traditional Market, Jambi City in 2024 - Cristine Sianturi; Marta Butar Butar; Oka Lesmana; Willia Novita Eka Rini; Adelina Fitri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Contact dermatitis is the occurrence of dermatitis (skin inflammation) accompanied by spongiosis or intracellular edema in the epidermis due to interactions between the skin and irritants or chemicals. These ingredients can be toxic or allergic. This study aims to determine the factors that can cause the incidence of irritant contact dermatitis in fish traders. This research was conducted in January – February 2024 using a quantitative approach with a cross sectional design. The sample in this study amounted to 65 people obtained using simple random sampling techniques. Data collection uses questionnaires and examinations by health workers. The data analysis method uses the Chi-Square test. The results of the study showed that there was a relationship between age (p= 0.002), personal hygiene (p= 0.005), length of exposure (p= 0.005), use of PPE (p= 0.001), and provision of clean water (p= 0.004) with the incidence of contact dermatitis to fish traders. There was no relationship between gender (p= 0.532) and length of service (p= 1.000) with the incidence of contact dermatitis in fish traders at Aur Duri Market, Jambi City.